2019
DOI: 10.1021/acs.nanolett.9b02869
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Optoacoustic Tracking of Single Moving Micro-objects in Deep Phantom and Ex Vivo Tissues

Abstract: Medical imaging plays an important role in diagnosis and treatment of multiple diseases. It is a field which seeks for improved sensitivity and spatiotemporal resolution to allow the dynamic monitoring of diverse biological processes that occur at the micro-and nanoscale. Emerging technologies for targeted diagnosis and therapy such as nanotherapeutics, microimplants, catheters, and small medical tools also need to be precisely located and monitored while performing their function inside the human body. In thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 54 publications
0
70
0
Order By: Relevance
“…As a next important step, it will be exciting to extend these efforts to whole organisms by integrating for example electromagnetic actuation to small animal bioimaging systems (e.g., fluoroscopy, ultrasound, infra-red coherence tomography and optoacoustic tomography) to assess feasibility for human trials. Notably, the magnetic actuators can be easily scaled-up but then the imaging and feedback control of the untethered microswimmers become more challenging owing to the current spatiotemporal resolution of~150 µm in real time when using cutting-edge ultrasound and optoacoustic imaging systems 28,[172][173][174][175][176] . In this regard, the increased size of individual microrobots over nanomedicines or using microrobot swarms could provide distinct advantages 119,[177][178][179] .…”
Section: Translatability Challengesmentioning
confidence: 99%
“…As a next important step, it will be exciting to extend these efforts to whole organisms by integrating for example electromagnetic actuation to small animal bioimaging systems (e.g., fluoroscopy, ultrasound, infra-red coherence tomography and optoacoustic tomography) to assess feasibility for human trials. Notably, the magnetic actuators can be easily scaled-up but then the imaging and feedback control of the untethered microswimmers become more challenging owing to the current spatiotemporal resolution of~150 µm in real time when using cutting-edge ultrasound and optoacoustic imaging systems 28,[172][173][174][175][176] . In this regard, the increased size of individual microrobots over nanomedicines or using microrobot swarms could provide distinct advantages 119,[177][178][179] .…”
Section: Translatability Challengesmentioning
confidence: 99%
“…Nonetheless, possible health concerns -such as with radioactive substances in diagnostic nuclear medicine -always need to be considered when a novel technique or combination of techniques is proposed. possibility of applying this technology in small animals for in vivo studies (Aziz et al 2019). The published works on sperm-hybrid micromotors discussed in this review are listed chronologically and summarized in Table 2.…”
Section: R92mentioning
confidence: 99%
“…In this case, spectral unmixing was applied to distinguish the signals by their specific absorption peaks. Another strategy to enhance the PA signal of injected micromotors is to stamp them with suitable and biocompatible contrast agents that absorb in a narrow and specific wavelength range, such as the ones shown previously by our group [35,36] with a strong absorption peak in the near infrared range.…”
Section: D Multiplexing In Vivomentioning
confidence: 99%
“…1 cm phantom and in ex vivo chicken tissue samples, highlighting the limits of the technique and showing the advantages of using nanomaterials as labels with unique absorption spectrum to improve micromotors' image contrast and molecular specificity. [35][36][37] In later studies, PAI was employed for guiding capsules containing catalytic micromotors in mice intestines, as well as to track swarms of magnetic spiral-like micromotors to treat induced subcutaneous bacterial infection, also in mice. [23,38] Both PAI studies showed the application of micromotors in vivo but there was no clear observation of single micromotor imaging in real-time in living mice, or the distinction between the structure and function of a single or few micromotors and their surrounding environment.…”
Section: Introductionmentioning
confidence: 99%